1980
DOI: 10.1901/jaba.1980.13-693
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Contingent‐interrupted Music in the Treatment of Disruptive Bus‐riding Behavior

Abstract: The present study evaluated the efficacy of using contingent‐interrupted music in treating the disruptive bus‐riding behavior of an 8‐year‐old profoundly retarded female. Music was played during each bus ride as long as the subject was sitting appropriately, and interrupted contingent upon each response defined as disruptive bus riding, during an ABCDCDCDA design. A significant reduction in disruptive bus riding occurred with each introduction of contingent‐interrupted music. The treatment procedure described … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

1986
1986
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…Results of the reward and time-out analyses suggest that decreased response levels were attributable to the removal of the sorting materials, which interrupted the ongoing sorting response. Contingent interruption of automatically reinforced behavior has been used to reduce the occurrence of such responses and has been reported as a punishment effect (e.g., Barmann, Croyle-Barmann, & McLain, 1980;Lerman & Iwata, 1996). Likewise, interruption of the sorting task appeared to function as punishment.…”
Section: Resultsmentioning
confidence: 99%
“…Results of the reward and time-out analyses suggest that decreased response levels were attributable to the removal of the sorting materials, which interrupted the ongoing sorting response. Contingent interruption of automatically reinforced behavior has been used to reduce the occurrence of such responses and has been reported as a punishment effect (e.g., Barmann, Croyle-Barmann, & McLain, 1980;Lerman & Iwata, 1996). Likewise, interruption of the sorting task appeared to function as punishment.…”
Section: Resultsmentioning
confidence: 99%
“…( 1998 ), Neave and Wolfson ( 2003 ) (All TS, and one naturalistic study) Contingent music Music played or stopped in real time, based on observed behavior of the individual or group Increased weight gain of babies, improved baby development possibly, work performance, academic achievement, attention and focus (ADHD symptoms down); reduced aggression Allen and Bryant ( 1985 ), Barmann and Croyle-Barmann ( 1980 ), Barmann et al. ( 1980 ), Bellamy and Sontag ( 1973 ), Blumenfeld and Eisenfeld ( 2006 ), Cevasco and Grant ( 2005 ), Cook and Freethy ( 1973 ), Cotter ( 1971 ), Davis et al. ( 1980 ), Dellatan ( 2003 ), Deutsch et al.…”
Section: Kernel Definition Derivation and Examplesmentioning
confidence: 99%
“…Entre os estudos que utilizaram a música como reforçador, há um grupo que objetivou mudar certos comportamentos tornando-os "adaptados" ou "produtivos" (Barmann, Croyle-Barmann, & Mclain, 1980;Wilson & Hopkins, 1973;Greene, Bailey, & Barber, 1981;Lowe, Beasty, & Bentall, 1983;Hume & Crossman, 1992). Um segundo grupo ocupou-se de comparar também o valor reforçador de alguns outros estímulos juntamente com os musicais (Ferrari & Harris, 1981;Thompson, Heistad, & Palermo, 1963;Vollmer & Iwata, 1991;Kennedy & Souza, 1995).…”
Section: Função Reforçadoraunclassified